Estrogenic Regulation of the SCF/c-KIT System in Prostate Cells: a Relationship with Prostate Cancer? - Figueira, Marília Isabel Neto (2014)
Prostate cancer (PCa) is the most common type of oncological disorder in men, for which an increasing incidence has been reported. Development and progression of PCa have been highly related with the circulating and intraprostatic hormonal milieu. Despite the classical role of androgens as stimulating agents in PCa growth, currently, estrogens also have been implicated in the prostate carcinogenesis. However, a duality for the possible role of estrogens in prostate cells has been gaining consistency over the last years. If some studies defend that estrogens are potential causative agents of PCa, other strong evidences indicate that these steroids may be protective against PCa. The tyrosine kinase receptor c-KIT and its ligand, the Stem Cell Factor (SCF) are powerful agents stimulating cell proliferation in a broad range of tissues, and the SCF/c-KIT interaction seems to play a crucial role in carcinogenesis. Moreover, it has been shown that estrogens modulate the expression of SCF/c-KIT system in several tissues, except the prostate. The present work aims to evaluate the role of estrogens regulating the SCF/c-KIT expression in human prostate cell lines and in rat prostate in vivo. The consequent effects on proliferation and apoptosis of prostatic cells will also be determined. Neoplastic (LNCaP, DU145 and PC3) and non-neoplastic (PNT1A) human prostate cell lines were cultured in presence or absence of 100 nM 17b-estradiol (E2) for different time periods. Adult male Wistar rats were daily injected with vehicle (control) or E2 (250 mg/day/kg) for 5 days. After treatment, animals were euthanized under anesthesia and prostates were collected, weighted and either fixed in 4 % paraformaldehyde or snap frozen in liquid nitrogen. The expression analysis of SCF and c-KIT in response to E2 was performed by means of real-time PCR, Western Blot and immunocito/histochemistry. The proliferation in rat prostate cells was estimated via fluorescent immunohistochemistry of Ki67. The protein ratio of Bax (pro-apoptotic)/Bcl-2 (anti-apoptotic), the expression of caspase-9, Fas and Fas- L, the enzymatic activity of caspase-3 and a TUNEL assay were used to evaluate apoptosis. The results obtained showed a decreased expression of both SCF and c-KIT in response to E2-treatment either in human prostate cells or rat prostate in vivo, which suggested a restricted proliferation of prostate cells in response to estrogens. This fact was confirmed in vivo by the diminished prostate weight and reduced Ki67 proliferation index observed in the E2-treated group. In addition, the enzymatic activity of caspase-3 was increased in response to E2, which indicates that estrogens induced apoptosis in rat prostate. The enhanced expression of the Fas system in the prostate of E2-treated animals suggests the involvement of the extrinsic pathway in the estrogen-induced apoptosis. In conclusion, the present work demonstrated that estrogens down-regulate the SCF/c-KIT system in neoplastic and non-neoplastic human prostate cells and in rat prostate in vivo. Moreover, estrogens have anti-proliferative and apoptosis-inducer effects in prostate exerted likely through the down-regulation of the SCF/c-KIT system. These findings also provided a body of evidence supporting the protective role of estrogens against development of PCa.